(untitled) (diségno, 2021)
Introduced by a Preface by Francesca Fatta, this interesting monographic volume by Massimiliano Ciammaichella investigates the relationship between the invention of scenography in Venice between the sixteenth and seventeenth centuries and the science of perspective, articulating the theme in three chapters (read more).